ANALISIS POKOK-POKOK MATERI PENDIDIKAN KARAKTER BERBASIS FOLKLOR BALI DALAM PEMBELAJARAN AGAMA HINDU - I Putu Suardipa (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2020)
In this research article, the objective of this research is to analyze the main points of educational material based on Balinese folklore in learning Hinduism in elementary schools. This study uses a qualitative research approach, with descriptive methods. The sample consisted of elementary school teachers who taught Hinduism in grades I, II, and III which are well known in Bali Province. Data were collected using a questionnaire. Data analysis using descriptive qualitative analysis techniques with percentages. The results of the study were to: First, the indicators of the types of Balinese folklore used in learning Hinduism in grades I, II, and III of elementary schools in Bali Province. Second, the character values contained in Balinese folklore used in learning Hinduism for grade I, II, and III elementary school students in Bali Province, third, whatever is relevant the character education values contained in Balinese folklore with the competencies required by Hindu Religion Subject in Elementary School.